Patronage and politics in a South African city: a case study of Nelson Mandela Bay. Issue 3 (2nd September 2018) - Olver, Crispian
ABSTRACT: A case study of a South African metropolitan municipality, Nelson Mandela Bay (NMBM), explores the dynamics between a political party in power and control over rents from public-allocation processes. The case study documents the weakening of the local state and political control of its allocation processes, linked to the parallel rise of a patronage-based business model within the African National Congress (ANC) as the local ruling party. Particular allocation processes that prove to be vulnerable are newly established programmes with as yet underdeveloped controls and institutional mechanisms. The paper reflects on experiences elsewhere in Africa and alternative analytical models to understand the interplay between rents, patronage and political power. The central features of the NMBM example are described in terms of the market forces unlocked by the South African transition to democracy. The paper concludes by looking at the importance of public institutions in circumscribing and directing markets.